PERSEPSI MASYARAKAT DAN PERANAN PERTANIAN PERKOTAAN DALAM PENURUNAN BIAYA KONSUMSI HARIAN RUMAH TANGGA - Veralianta Br Sebayang; Doni Sahat Tua Manalu; Wien Kuntari; Agief Julio Pratama; Helianthi Dewi; Daisy DSJ Tambajong (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
Urban farming is an activity of using unproductive land into productive land in the yard of the house. Urban farming can contribute to food security, hope food patterns, increase people's income and as a means of channeling hobbies. Urban farming is an alternative in increasing the productivity of home gardens to increase hopeful food patterns and reduce the cost of daily consumption expenditures for households. This study aims to determine the public perception of urban farming and to determine the contribution of urban farming to the decrease in daily consumption costs. This research was conducted in Margajaya Village, West Bogor District, Bogor City. Descriptive statistics are used to determine people's perceptions of urban farming while inferential statistics are used to test the hypothesis that urban farming can reduce household daily consumption costs by 5 percent. The results showed that people who understand about urban farming as much as 87.23%. The results of testing the hypothesis that the portion of daily consumption cost reduction of more than 5 percent can be accepted at the 95% confidence level. This indicates that urban farming has an important role from an economic perspective. Socialization of urban farming programs is a necessity, to increase food security, it has the potential to increase people's income and reduce poverty in urban areas